Multi-classification for Predicting Alzheimer's Disease Using 1.5T1-weighted MRI Imaging and Deep Learning 2D CNN - Shahad Shahad Haitham Ali (Indonesian Journal Publisher, 2025)
Medical imaging holds the pivotal role in clinical diagnosis, education, research work, and treatment of medicine. Medical professionals are tasked with analyzing and interpreting high-level medical data, which is extremely difficult in nature due to the intricate nature of medical images. Deep learning techniques are emerging as strong tools, yielding promising and correct results in the analysis of medical data. Alzheimer's disease, which affects one in every ten individuals aged 65 and above, is a central focus where such advancements are aimed. Artificial intelligence has proved capable of distinguishing between healthy brains and Alzheimer's disease-affected brains. The etiology of the disease lies in abnormal proteins accumulating inside and outside neuronal cells, causing irreparable loss of memory. Alzheimer's disease is the most prevalent form of dementia, and